Infantile presentation of the canal of Nuck hernia containing uterus and ovary: a case report - Hidayatullah Hamidi, MD; Mariam Rahimi, MD (Radiology Case Reports, 2020)
Indirect inguinal hernias of the canal of Nuck containing the uterus and the ovary is rare entity in girls presenting as labia major masses at infancy and early childhood. Authors present a case of the canal of Nuck hernia in a 5-month-old girl presented as palpable lump in the right labia majora which was diagnosed by ultrasonography. Ultrasound is the noninvasive diagnostic modality of choice in for evaluation of palpable external genital masses in children.